Effect of non-traumatic first trimester per vaginal bleeding on maternal and fetal outcomes in Indian tertiary care teaching hospital - Arora, Shweta; Tanveer, Raeesa; Gulati, Rachit (International Journal Of Community Medicine And Public Health, 2023)
Background: Aim of study was to assess the maternal and perinatal outcomes in first trimester vaginal bleeding. Methods: This prospective observational study was done on 112 patients with first trimester vaginal bleeding at a tertiary care teaching hospital in South India over a period of two years. All the patients who satisfied the inclusion and exclusion criteria were evaluated for the outcomes like hypertensive disorders, post partum and anter partum haemorrhage, rupture of menbranes, anemia, gestational diabetes, pre term delivery, low birth weight, small for gestational age, NICU admissions, intra-uterine growth restriction and mode of delivery. Results: Maximum patients with bleeding per vagina in first trimester belonged to 26-30 years age group out of which majority had spotting. No specific significance was found to be associated between gravida score and bleeding or bleeding types. Out of 75 patients who continued pregnancy, 57 (76.0%) patients had one or the other complication in pregnancy which was significant (p<0.05). Regarding fetal outcomes, 19 had preterm delivery, 10 were LBW while 4 were SGA, 26 required NICU admissions and 8 had IUGR. 48 patients had recurrent bleeding PV which showed no significant correlation with abortion or APH. Conclusions: Study shows that per vaginal bleeding in first trimester may lead to maternal and foetal complications. We recommend training pregnant women regarding those complications and their prevention.